Equivalent Structures for Nonlinear-Signal Cable Networks - Ciufudean, C.; Larionescu, A.; Filote, C. (Elektronika ir Elektrotechnika, 2009)
This paper focuses on the effects of nonlinearities of electrical signals driven through cable networks. Some new methods derived from original models are proposed here in order to avoid the damages caused by nonlinearities induced by cable networks. Ill. 9, bibl. 9 (in English; summaries in English, Russian and Lithuanian).